2010
DOI: 10.1055/s-0030-1267976
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Neurodevelopmental Impairment in Neonates Surgically Treated for Necrotizing Enterocolitis: Enterostomy Associated with a Worse Outcome

Abstract: The results suggest that an enterostomy in SNEC patients could be associated with worse neurodevelopmental outcomes by the age of 6-13 years compared to a primary anastomosis, although the severity of illness was comparable between both groups. Further studies are needed to prevent selection bias and to elucidate the impact of abdominal surgical factors on neurodevelopmental outcome and the underlying pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…NEC remains a disease with high mortality even with aggressive treatment 12) . Additionally, NEC requiring surgical treatment lead to growth and developmental disorders in VLBW infants 13,14) . The incidence of NEC varies with reporters.…”
Section: Discussionmentioning
confidence: 99%
“…NEC remains a disease with high mortality even with aggressive treatment 12) . Additionally, NEC requiring surgical treatment lead to growth and developmental disorders in VLBW infants 13,14) . The incidence of NEC varies with reporters.…”
Section: Discussionmentioning
confidence: 99%
“…(A) Demographics (gestational age, birth weight, sex); (B) Other known risk factors for NEC or bowel perforation (formula feeding and lack of breast milk exposure [19]; maternal syphilis [20]; weight below third centile for gestational age [21]; cardiac anomalies [22]; nonsteroidal anti-inflammatory (Nurofen) received for patent ductus arteriosus closure [23,24]; blood transfusion in previous 48 hours [25]; umbilical line placement and polycythemia [26]; multiple birth; no antenatal steroid exposure [27,28]; hypoxic events causing impaired bowel blood flow [29] including hypoxic ischemic encephalopathy; inotrope exposure preceding NEC development; maternal cocaine or methamphetamine abuse [29,30]; maternal preeclampsia/hypertension, elevated liver enzymes, low platelets; and hypogylycemic insults [31] as well as neonatal and maternal perinatal sepsis [32]); (C) Disease presentation and surrogate markers for disease severity (bacteremia detected on blood culture); radiologic markers of severe NEC, SNAPPE II, and CRIB II scores [33][34][35][36]; metabolic parameters (pH, base excess, lactate, serum sodium, hyperglycemia), hematologic (white cell, polymorph, platelet count, international normalized ratio [INR], C-reactive protein levels [37][38][39]) and hemodynamic parameters (inotrope requirements [40]); and fulminant presentation (gangrenous bowel within 24 hours of presentation) [41]; (D) Surgical findings (total gut necrosis, isolated perforation as opposed to multiple perforations [42,43]) and type of surgery done (peritoneal drains [44], primary anastomosis [45], stoma [46]). Surgery was performed either by or under the supervision of experienced pediatric surgeons according to a departmental protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In another report, the authors also suggested that VLBW infants who survive NEC were at risk for impairment of growth and neurodevelopment [15]. More recently Ta et al [16] reported that, an enterostomy in patients with NEC surgery could be associated with worse neurodevelopmental outcomes by the age of 6-13 years compared to a primary anastomosis, although the severity of illness was comparable between both groups.…”
Section: Discussionmentioning
confidence: 99%